Housing prices and investment: an assessment of China's inland-favoring land supply policies. Issue 1 (2nd January 2017) - Han, Libin; Lu, Ming
ABSTRACT: Since 2003, China's central government has allocated more construction land-use quotas to inland provinces than elsewhere in an attempt to balance the growth gap between its coastal and inland regions. Here, firm-level data from 2001 to 2007 were used to determine how this change in land policy has affected firms' investments and housing prices. Results have shown that cities in which land-use quotas decreased experienced faster housing price growth than the cities in which land-use quotas increased after 2003. This sharp change in policy also highlighted two major channels of the effects of housing prices on investment by firms. The results show that higher housing prices increased firms' investment by providing a source of more valuable collateral, while crowding out fixed capital investment. The net effect of housing prices on investment is negative and limiting economic growth.